Lymph node staging in extracranial head and neck cancer with FDG PET – appropriate uptake period and size-dependence of the results - Brink, I.; Klenzner, Th.; Krause, Th.; Mix, M.; Ross, U. H.; Moser, E.; Nitzsche, E. U. (Nuklearmedizin - NuclearMedicine, 2002)
Aim: Identification of a rationale for the appropriate uptake period for static clinical extracranial head and neck PET imaging and evaluation of the diagnostic accuracy of such an optimized FDG PET approach for lymph node staging in the head and neck region. Methods: In a subset of 5 patients, kinetic tumour studies were performed in order to identify the cellular activity plateau phase of FDG accumulation for head and neck cancer. Seventy-eight consecutive patients (11 women, 67 men; mean age ± SD: 55 ± 11 years; range, 36-78 years), presenting with histologically proven squamous cell carcinoma and sonographically detected lymph nodes in 86 neck sides, underwent clinically indicated FDG PET imaging. PET results were compared to those derived from histological examinations and follow-up imaging results after 6 months in order to calculate sensitivity and specificity for lymph node staging. Results: FDG kinetics in head and neck cancer indicate that the cellular activity plateau of FDG accumulation is reached after an uptake period of 90 min. Using this protocol metastatic involvement of neck sides with lymph nodes less than 1 cm in diameter was correctly identified with a sensitivity of 71.4% and a specificity of 92.3%. Sensitivity increased with the lymph node diameter (1.1-1.5 cm 83.3%, 1.6-2.0 cm 100%, > 2 cm 88.9%). Conclusion: The appropriate uptake period for static clinical extracranial head and neck PET imaging that allows measurements in the activity plateau phase is about 90 min. FDG PET may add some significant information regarding metastatic spread into regional lymph nodes.
Keywords: Head and neck cancer; lymph node staging; 18F-FDG PET; metastases